Research progress in mechanisms, influence factors and improvement routes of chloride binding for cement composites - He, Haijie; Qiao, Hongxia; Sun, Tianying; Yang, Haiming; He, Chuang (Journal of Building Engineering, 2024)
Chloride-induced corrosion of steel reinforcement is a major cause of durability degradation for reinforced concrete (RC) structures. Chloride binding approach is recognized as one of the most economically effective methods to address the above issue. However, there is still a lack of comprehensive and up-to-date reviews in the field of chloride binding. Therefore, a thorough analysis of current studies on chloride binding is required. This review aims to provide a comprehensive outline from three aspects: mechanisms, influence factors, and improvement techniques of chloride binding for cement-based materials. Specifically, two kinds of chloride binding mechanisms are systematically introduced. Subsequently, various influence factors of chloride binding are comprehensively analyzed. Furthermore, effective methods to enhance chloride binding performance are introduced. Finally, the challenges and prospects in the field of chloride binding for cement-based materials are discussed in depth. This review is expected to assist researchers in better understanding chloride binding and would provide a reference for designing effective anti-chloride-corrosion measures for steel reinforcement and predicting the service life of RC structures. [Display omitted] •Chloride binding mechanism of cement matrix is comprehensively outlined.•Various influence factors of chloride binding are deeply discussed.•Enhancement methods of chloride binding are systematically introduced.•Challenges and prospects of chloride binding are rationally proposed.